PEMANFAATAN APLIKASI SOLITE KIDS TERHADAP KEMAMPUAN BERBAHASA ARAB SISWA KELAS V MI AL QUR’AN AL HIKMAH - fatimah, fatimah; Al ‘Am, Maftah Rozani; Rohmah, Nur Hidayatur (Al-Fakkaar, 2024)
In learning Arabic accompanied by digital developments, the innovative and technology-based learning is needed to face the challenges of the millennial era 4.0. This effort aims to keep pace with technological advances so as to have a positive impact on the field of education. Android-based learning media such as the Solite Kids app is the answer to this needs. This application is in the form of a game and is equipped with various features, including the Little One Learning Series. This research is classified as qualitative research using observation, interviews, and literature studies as sources. The initial findings are (1) the students look hyper active in the classroom, (2) the students tend to think Arabic is a difficult and boring lesson, (3) arabic is considered an unimportant subject, (4) arabic language skills are still far from average (far from the KKM standard). With these findings, the purpose of using solite kids is to eliminate the mindset that learning Arabic is difficult and boring. Solite kids, as a learning tool, is designed to provide an interactive and engaging learning experience. Based on the above findings, the researchers conducted research by utilizing the solite kids application to improve the arabic language skills of Islamic Elementary School of Al Qur'an ‘Al Hikmah’ students, with the result that the application has a positive impact on Arabic language learning, namely (1) high enthusiasm and interest of students, (2) increased student learning motivation, (3) visible learning progress, (4) collaboration and social interaction between students, and (5) feedback on the material. By using the solite kids, learning results were obtained with a balanced percentage, namely 75% of these fifth grade students were very enthusiastic about solite kids learning, and 25% were quite enthusiastic about using the solite kids application.